Perspective methods of pipeline construction in arctic condition on an example of trans alaska pipeline system; Международный научно-исследовательский журнал; № 5 (5), ч. 2 - Chukhareva N. V. Natalia Vyacheslavovna (2012, 2012)
He exploitation of the Arctic region depends on meeting the challenges of pipeline design, construction and operation which to be solved by modern science and petroleum industry. The objective of this research is to identify the most perspective technologies to be applied in Arctic pipeline construction.